2009
DOI: 10.1007/s00266-009-9359-3
|View full text |Cite
|
Sign up to set email alerts
|

Unacceptable Results with an Accepted Soft Tissue Filler: Polyacrylamide Hydrogel

Abstract: A wide range of complications seen among our patients showed that polyacrylamide hydrogel may not be as safe and biocompatible as it was thought previously. Both patients and physicians must be aware of the potential side effects of polyacrylamide hydrogel before gel administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 17 publications
0
33
0
2
Order By: Relevance
“…Inadvertently, the gel can be injected into the pectoralis muscle. The gel can then extravasate into the extrapleural space, as seen in case #2 [6]. PAAG can spread via direct extension to create subcutaneous nodules in the inframammary fold, axilla, sternum, and infraclavicular region if the gel is injected in the subcutaneous plane [7].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Inadvertently, the gel can be injected into the pectoralis muscle. The gel can then extravasate into the extrapleural space, as seen in case #2 [6]. PAAG can spread via direct extension to create subcutaneous nodules in the inframammary fold, axilla, sternum, and infraclavicular region if the gel is injected in the subcutaneous plane [7].…”
Section: Discussionmentioning
confidence: 97%
“…Under the microscope, inflammatory foreign body reactions to the injected material can be appreciated. Inflammatory reaction features infiltration by lymphocytes and plasma cells, histiocytic cells, and foreign body-type multinucleated giant cells walling off PAAG [6,8]. Christensen et al [21] described histological findings of the breast tissue bordering the gel showed three different patterns: large collections of gel gave rise to a thick, soft-looking cellular membrane of macrophages and foreignbody giant cells; medium-size deposits were surrounded by just a thin layer of macrophages; and small deposits were not associated with any reaction in the surrounding tissue.…”
mentioning
confidence: 99%
“…Christensen et al 7 reported a volume-dependent inflammatory reaction to polyacrylamide injection for breast augmentation; histological analysis showed that large volumes were associated with foreign-body giant cell reaction. Manafi et al 8 described 98 consecutive patients presenting with complications from polyacrylamide injection, most commonly inflammation, including 9 from buttock or leg injections. In their series, all patients were treated with an incision, drainage, and irrigation; none required a radical excision.…”
Section: Discussionmentioning
confidence: 99%
“…This complication may be, transient, nonsignificant (pain, hematoma), surgical route error (irregularity, gel accumulation, asymmetry), infectious (abscess), host tissue reaction (foreign body granuloma, edema, inflammation, redness, sensitivity), and miscellaneous such as gel migration, lumpiness, and gel indurations [9, 1114]. …”
Section: Introductionmentioning
confidence: 99%